Strategi Event Perkumpulan Beon Tek Bio Terhadap Festival Peh Cun di Kota Tangerang - David Soni Oksapianus; Mochammad Mirza; Ukon Furkon Sukanda; Alamsyah Alamsyah (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Tambur Peh Cun is a tradition in the form of a festival that still continues today among the Chinese community in Tangerang, Banten. The term Peh-Cun means “boat racing” in Hokkien and consists of two words “Peh” which means “Paddle” or “Paddle” and “Cun” which means “Boat”. Tambur Peh-Cun or also known as